PENGARUH PERMEN KUNYAH MENGANDUNG GAMBIR (Uncaria gambir [Roxb.]) TERHADAP PENURUNAN KOLONI BAKTERI DAN PEMBENTUKAN PLAK GIGI - Siti Rusdiana Puspa Dewi; Rindit Pambayun; Budi Santoso; Rini Bikarindrasari (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2023)
Background. Dental and gum disease is a health problem faced by many countries around the world. Dental and gum diseases begin with the formation of plaque on the tooth surface, as a result of the activities of bacteria in the oral cavity. Elimination of the bacteria as caries causal has been done in many ways, one of them by using plant extracts which have anticariogenic activities, such as gambir (Uncaria Gambir [Roxb.]). The aim of this study was to determine the effect of chewing candy containing gambir on the decrease of bacterial colonies and dental plaque formation. Methods. A Pretest-Posttest Control Group Design had been conducted in SMPN 17 of Junior High School in Palembang and Province’s Health Laboratory of South Sumatera, Indonesia. The population consisted of 50 participants, divided into 5 groups. Each group was chewing with 5%, 7.5%, 10% extract-gambir candies, no chewing candies, and chewing sucrose’s candies. Data were analyzed by using SPSS vers 22. Result. The results showed that all candies containing gambir extract were able to reduce the formation of dental plaque and to decrease the bacterial colonies in saliva. The best effect of this study was 10% extract-gambir candies. Conclusion. It can be concluded that extract-gambir candies were effective in the decline of dental plaque formation and bacterial colonies.